2015
DOI: 10.5194/acp-15-173-2015
|View full text |Cite
|
Sign up to set email alerts
|

Air quality and atmospheric deposition in the eastern US: 20 years of change

Abstract: Abstract. Data collected in the eastern US between 1990 and 2009 at 34 paired dry and wet monitoring sites are examined. A goal is to evaluate the air quality impacts occurring between 1990 and 2009 that are associated with concurrent legislatively mandated changes in emissions. Four 5-year periods, 1990-1994 (P1), 1995-1999 (P2), 2000-2004 (P3), and 2005-2009 (P4) are considered, with a primary focus on P1-to-P4 changes. Results suggest that legislatively mandated air pollution mitigation strategies have be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 42 publications
8
93
0
Order By: Relevance
“…In the United States, the National Atmospheric Deposition Program/National Trends Network (NADP/NTN; https://nadp.slh.wisc.edu/ntn) provides the nation's primary WD data. These observed WD values are often used to estimate past and current loads of acidic (S + N) and nutrient (N) deposition on sensitive ecosystems for critical loads exceedance studies in the United States (Nanus et al, ; Sickles & Shadwick, , ). Using NADP/NTN data from 1985 to 2012, Du et al () found a positive trend in ammonium WD at the national scale and a significant negative trend in nitrate WD, especially in the Northeast.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the National Atmospheric Deposition Program/National Trends Network (NADP/NTN; https://nadp.slh.wisc.edu/ntn) provides the nation's primary WD data. These observed WD values are often used to estimate past and current loads of acidic (S + N) and nutrient (N) deposition on sensitive ecosystems for critical loads exceedance studies in the United States (Nanus et al, ; Sickles & Shadwick, , ). Using NADP/NTN data from 1985 to 2012, Du et al () found a positive trend in ammonium WD at the national scale and a significant negative trend in nitrate WD, especially in the Northeast.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of US National Atmospheric Deposition Program (NADP) observations (24) illustrates decreases in US wet nitrate deposition and increases in wet ammonium deposition in many regions. Focusing on the Midwest and Eastern United States, Sickles and Shadwick (25) reported that reductions in NO x emissions have decreased oxidized nitrogen dry and wet deposition and that particulate ammonium concentrations now exceed concentrations of particulate nitrate plus gaseous nitric acid in the region. Ammonia gas was not considered in their study.…”
Section: Significancementioning
confidence: 99%
“…The decline in SO 4 concentrations vs. emissions or ambient SO 2 tends to be linear, but less than 1:1 (e.g. Hidy et al, 2014;Sickles and Shadwick, 2015). As discussed later, the difference between the responses of ambient SO 2 and SO 4 is identified with the atmospheric production of SO 4 during dispersal from primary SO 2 sources.…”
Section: Us National Ambient Sulfur Oxide Trendsmentioning
confidence: 99%
“…Dry deposition rates have been estimated typically for relatively smooth surfaces sometimes covered with low vegetation; forested, hilly and mountainous terrain have not been characterized with the same certainty. (e.g., Sickles and Shadwick, 2015). Trends in dry deposition have been found to follow trends in ambient concentrations of SO x , accounting for surface inhomogeneities in spatially differentiated models.…”
Section: Us National Ambient Sulfur Oxide Trendsmentioning
confidence: 99%